Influence of fasteners and connections flexibility on deflections of steel building including the stressed skin effect - Korcz, Natalia; Urbańska-Galewska, Elżbieta (Technical Sciences, 2018)
The paper presents the analysis of the influence of fasteners and connections flexibility on displacements of symmetrical single-bay pitched-roof steel building, including trapezoidal cladding acting as a diaphragm. The purpose of the article was to compare numerical models with and without taking into consideration fasteners and connections flexibility in order to observe the differences in transverse stiffness of the building during modifying model from the simple one to more complex and precise. The analyses were carried out for the 3D structure. Fasteners and connections were substituted by equivalent beam finite elements. Corrugated sheets were replaced by three types of equivalent orthotropic shell models and the influence of the choice of the model on the stiffness of the building was observed. The results showed that in the analysed structure the flexibility of fasteners and connections has negligible effect on transverse displacements of the building in the case of four sides fastening of the sheeting, however in the case of two sides fastening the influence significantly increases.